2011
DOI: 10.1097/ajp.0b013e31821962b4
|View full text |Cite
|
Sign up to set email alerts
|

Dose-specific Effects of Transcutaneous Electrical Nerve Stimulation (TENS) on Experimental Pain

Abstract: The level of hypoalgesic efficacy of TENS is clearly dependent on TENS parameter combination selection (defined in terms of intensity, frequency, and stimulation site) and experimental pain model. Future clinical RCTs may consider these TENS dose responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 97 publications
1
51
0
6
Order By: Relevance
“…TENS efficacy has been shown in pressure pain, intense experimental pain and thermal pain models (Claydon et al, 2011). TENS efficacy has been shown in pressure pain, intense experimental pain and thermal pain models (Claydon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…TENS efficacy has been shown in pressure pain, intense experimental pain and thermal pain models (Claydon et al, 2011). TENS efficacy has been shown in pressure pain, intense experimental pain and thermal pain models (Claydon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled clinical trials have clearly demonstrated that TENS has a specific antalgic effect [14], but the intrinsic mechanism remains largely unknown [5]. For this reason, on the clinical ground, TENS is largely used by trial and error, and the optimal setting of stimulation parameters is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the increase in blood flow in the pelvis after PTNS, a decrease in blood flow in the uterine arteries occurred at stimulation with higher frequency at the site treated with PTNS (43). TENS research has shown better results on pain at higher frequencies and intensities (44).…”
Section: Discussionmentioning
confidence: 94%